Analysis of Teacher Strategies in Improving Students' Critical Thinking Skills in Pancasila Education Subjects, Pancasila Practice Material for Grade 2 Elementary Madrasah - Dwi Rahayu Irfani; Nur Mala Jenisa (Konsultan Jurnal Ilmiah Indonesia, 2026)
This study aims to analyze the strategies implemented by teachers in improving students' critical thinking skills in the Pancasila Education subject, especially the material on the Implementation of Pancasila in grade 2 of Madrasah Ibtidaiyah. The background of this study is based on the low critical thinking skills of students in elementary schools which hinders their ability to understand Pancasila concepts in depth and contextually. The research method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects consisted of teachers who teach the Pancasila Education subject and grade 2 students as participants. The results of the study show that teachers use a variety of learning strategies, including: a question-and-answer approach that stimulates student reflection, problem-based learning, and the use of relevant media and teaching aids. These strategies have proven effective in enhancing students' critical thinking skills through active engagement, group discussions, and analytical thinking evaluations. These findings form the basis for the recommendation that implementing varied and contextual learning strategies is crucial for fostering the development of critical thinking skills in students from an early age. The implications of this research are expected to enrich the practice of Pancasila Education learning at the MI level and contribute to efforts to improve the quality of character education in elementary schools.